Dansa i moralitat medieval en Francesc Eiximenis: Lo Libre de les Dones. - DALMAU MARTÍNEZ, XAVIER (Scripta)
In this study we revise the quotations on dance that appear in Lo Libre de les Dones by Francesc Eiximenis. This is a description-based analysis and exemplification to outline medieval Catalan morality from a point of convergence between dance and morality, dividing the quotations into good dances (dances to God, to the angels and dances in paradise) and the wicked dances (dances of sin and luxury, and dances against morality). This is how we analyse the dance-literature binomial to understand previous societies, rituals, thoughts, and ancient traditions that have been transported through time with folklore, traditional culture and the Church, and which form part of our cultural wealth and our identity as people.